PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH DENGAN PEMBELAJARAN LEARNING CYCLE DAN KONVENSIONAL PADAMAHASISWA PRODI PENDIDIKAN MATEMATIKA FKIP UST - Tri Astuti Arigiyati; Istiqomah Istiqomah (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
This study aims to determine differences in problem solving skills with the learningcycle and conventional models in Mathematics Education Programm UST. This study design is a randomized pretest-posttest control group design. The sample was a student of fourth semester. Data collected by the testing techniques that comprise the initial test (pretest) and final test (posttest). Instruments in this research is a test instrument that consists of 4 questions about the pretest and posttest 5. The trials instruments include validity, different power, test difficulty levels, and reliability testing. Data analysis techniques include equality test average, which is the prerequisite test normality and homogeneity test, and analysis of the N gain using the t test. The results showed that there are differences in problem-solving abilities with learning model and conventional learning cycle. It was seen from the significant value of the index gain = 0.000 <Î± = 0:05. Based on the average ability of mathematical reasoning and problem solving shows that the model Learning Cycle better than conventional models.